Stress exposure status and associated factors among Chinese People's Armed Police personnel: A cross-sectional study - Li, Nan; Zhang, Yongzhong; Hou, Shike (Frontiers in Psychiatry, 2022)
Background: MG (Mass gathering) deployment is one of the primary duties of Chinese People’s Armed Police (PAP) personnel. Due to prolonged and repeated deployments in difficult conditions and harsh climates, military personnel are exposed to multiple stressors. Objectives: This study aims to understand the stress exposure status of armed police personnel during MG deployment and to explore its influencing factors. Methods: A cross-sectional study was conducted among PAP in 2021. We used a cluster random sampling to select 960 PAP personnel. Binary logistic regression was used to examine whether the stress exposure status was associated with factors such as demographics, health service utilization, and MG deployment. Results: Among 960 PAP personnel，83% of PAP personnel participated in MG in the past month, and 23.1% of PAP personnel suffered stress. The chi-square test showed that there were significant differences in MG ’cycle time (p<0.05). The binary logistic regression results showed that satisfaction with medical skills(p=0.008), satisfaction with health environment(p=0.031), satisfaction with medicine (OR=0.640, 95%CI:0.436,0.938), seeking health services (OR=5.36, 95%CI:2.316,12.402) were associated with stress exposure status. However, age and Length of military service education did not have any association with the stress exposure status of PAP personnel in this study. Conclusion: This study demonstrated that stress exposure status among PAP personnel was associated with MG deployment, and health service utilization. These findings can help policy-makers and clinicians to relieve the stress of the armed police personnel, as well as provide a basis for developing military health service security plans.